Implementasi Metodologi Agile Software Development pada Proyek Perangkat Lunak - handrie noprisson (LPPMPP Yayasan Sejahtera Bersama Bengkulu, 2023)
This research is a systematic literature review using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) as a method to gather literature on agile software development methodology from Google Scholar. The result of this study is a summary of 11 articles related to Agile software development. The recommendation of this study is the use of the GLUX framework. GLUX framework integrates Lean UX into Scrum to improve the sustainability of the rapid software development process. It aims to promote a user-centric mindset and collaborative UX activities during the development process using gamification techniques. GLUX is about self-reliant teams, creating a motivating environment, and fostering teamwork.